Love is my savior : the Arabic poems of Rumi - Jalāl al-Dīn Rūmī, Maulana, 1207-1273.; Akhtarkhavari, Nesreen; Lee, Anthony A., 1947- (East Lansing : Michigan State University Press, 2016)
This new volume of Rumi's works, the first-ever English translation of his Arabic poems, will be exciting for the newcomer to Rumi's verses as well as to readers already familiar with his mystical philosophy. The poems take the reader on a journey of spiritual exploration, ecstatic union, cruel rejection, and mystic reconciliation. Rumi reveals his soul and welcomes everyone to his spiritual feast.
Glad Tidings!Your Wine Lights the World; Peace Is the Path; Hidden Beauty; I Climbed to Heaven; Good News!; Judgment Day; Appendix.
English translations of 33 Arabic poems and fragments, taken from the first 1010 poems in Rumi's Divan-e Shams.
Includes bibliographical references.
Includes poems in Arabic with English translation on facing pages.
JSTOR
Keywords: Jalāl al-Dīn Rūmī, -- Maulana, -- 1207-1273 -- Translations into English; Jalāl al-Dīn Rūmī, -- Maulana, -- 1207-1273 -- Translations into English; Jalāl al-Dīn Rūmī, -- Maulana, -- 1207-1273; FICTION -- General; poetry; Poetry; Translations; Poetry; Poésie.